A genius for money : business, art and the Morrisons - Dakers, Caroline (Yale University Press, 2011)
This is the spectacular rags-to-riches story of James Morrison (1789-1857), who began life humbly but through hard work and entrepreneurial brilliance acquired a fortune unequalled in nineteenth-century England. Using the extensive Morrison archive, Caroline Dakers presents the first substantial biography of the richest commoner in England, recounting the details of Morrison's personal life while also placing him in the Victorian age of enterprise that made his success possible.An affectionate husband and father of ten, Morrison made his first fortune in textiles, then a second in international finance. He invested in North American railways, was involved in global trade from Canton to Valparaiso, created hundreds of jobs, and relished the challenges of "the science of business". His success enabled him to acquire land, houses, and works of art on a scale to rival the grandest of aristocrats.